Kinetic relaxing processes in collective dynamics of pure liquids - Bryk, T.; Mryglod, I. (Condensed Matter Physics, 2004)
The role of nonhydrodynamic relaxing processes in collective dynamics of pure liquids is studied within a generalized collective modes approach. A five-variable model of generalized hydrodynamics is solved analytically in long-wavelength limit. Among five collective modes we found three hydrodynamic and two relaxing kinetic excitations. Two latter ones describe the viscous and heat relaxation in liquid. A comparison of analytical results and molecular dynamics data is performed for a Lennard-Jones fluid and a liquid metal. A crossover from standard hydrodynamics to molecular regime in relaxational behaviour of simple liquids is discussed.